Development of a novel epigeic-anecic-based polyculture vermireactor for efficient treatment of municipal sewage water sludge. (4th February 2008) - Suthar, Surindra
The potential of vermireactors, based on polyculture and monoculture system, was evaluated by using substrate consisted of domestic sewage sludge mixed with sugarcane trash, under laboratory conditions. Polyculture reactor was designed by using an epigeic (Eisenia fetida) and an anecic (Lampito mauritii) species of earthworm, while monoculture reactor had E. fetida only. Comparatively the end product i.e., vermicompost obtained from polyculture reactor showed the better concentration of nutrients and lower metal levels than monoculture reactor. Polyculture vermirector showed greater dehydrogenase activity and microbial biomass N, possibly related to the better microclimatic conditions in it. Results indicate that the polyculture vermireactor, especially designed by using at least one burrowing earthworm (endogeic or anecic) not only accelerates the mineralisation process, but at the same time also enhances the microbial activities in reactor.